2022
DOI: 10.14348/molcells.2022.0097
|View full text |Cite
|
Sign up to set email alerts
|

Recent Progress in Regulation of Aging by Insulin/IGF-1 Signaling in Caenorhabditis elegans

Abstract: Caenorhabditis elegans has been used as a major model organism to identify genetic factors that regulate organismal aging and longevity. Insulin/insulin-like growth factor 1 (IGF-1) signaling (IIS) regulates aging in many species, ranging from nematodes to humans. C. elegans is a nonpathogenic genetic nematode model, which has been extensively utilized to identify molecular and cellular components that function in organismal aging and longevity. Here, we review the recent progress in the role of IIS in aging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 93 publications
1
22
0
Order By: Relevance
“…Despite some evidence that D. nobile activates the Nrf2 pathway to exert its biological activity [ 11 , 54 , 55 ], we discovered that DnAE did not increase skn-1 expression. Daf-16 activation and Daf-2 degradation are the primary regulators of the IIS pathway that prolong the lifespan of C. elegans [ 56 ]. According to our findings, DnAE promoted DAF-16 entry into the nucleus through the cytoplasm and enhanced the expression of daf-16 and its downstream regulatory genes sod-3 , ctl-1 , and gst-4 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite some evidence that D. nobile activates the Nrf2 pathway to exert its biological activity [ 11 , 54 , 55 ], we discovered that DnAE did not increase skn-1 expression. Daf-16 activation and Daf-2 degradation are the primary regulators of the IIS pathway that prolong the lifespan of C. elegans [ 56 ]. According to our findings, DnAE promoted DAF-16 entry into the nucleus through the cytoplasm and enhanced the expression of daf-16 and its downstream regulatory genes sod-3 , ctl-1 , and gst-4 .…”
Section: Discussionmentioning
confidence: 99%
“…However, we observed that daf-2 and daf-16 genes are essential for kahweol’s lifespan-extending effect. This indicates that kahweol’s impact on lifespan is closely associated with regulating insulin signaling, DAF-2, and its major downstream transcription factor, DAF-16, as the IIS pathway plays a critical role in coordinating growth, metabolism, and lifespan in C. elegans ( Altintas et al, 2016 ; Lee and Lee, 2022 ). In C. elegans , activation of DAF-2 results in phosphorylation of transcription factor DAF-16, preventing it from translocating in the nucleus, leading to a shorter lifespan than wild-type ( Venz et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, inhibition of DAF-2 leads to activation of DAF-16 without phosphorylation, which then translocates DAF-16 into the nucleus ( Lamitina and Strange, 2005 ). The activation of DAF-16, the ortholog of mammalian FOXO transcription factors, is a key downstream target of the IIS pathway that improves longevity by regulating the expression of a wide array of target genes involved in stress response, metabolism, and cellular homeostasis ( Altintas et al, 2016 ; Lee and Lee, 2022 ). This suggests that the lifespan extension effect of kahweol results from the complex interplay with the IIS pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical descriptions of the top markers of ageing, which are currently being investigated, include the following parameters [ 24 ]: DNA copy number, telomere length, global DNA methylation, Hsp70 and Hsp72, insulin-like growth factor 1 (IGF-1) [ 41 , 42 ], SIRT1 (Sir2) as an NAD + -dependent deacetylase playing critical roles in a broad range of biological events [ 43 ] and a deregulated nutrient-sensing level, GDF-15, CD4 + , and CD8 + cell percentages [ 44 ] as a cellular senescence level [ 45 , 46 ], and circulating osteogenic progenitor (COP) cells as a marker of stem cell exhaustion. Next in this line are the levels of IL-6 [ 47 ], CRP, and TNF-alpha as evidence of altered intercellular communication [ 48 ].…”
Section: Biomarkers Of Ageingmentioning
confidence: 99%